2014
DOI: 10.1093/nar/gkt1387
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of alternative splicing events regulated by SRSF10 reveals position-dependent splicing modulation

Abstract: Splicing factor SRSF10 is known to function as a sequence-specific splicing activator. Here, we used RNA-seq coupled with bioinformatics analysis to identify the extensive splicing network regulated by SRSF10 in chicken cells. We found that SRSF10 promoted both exon inclusion and exclusion. Motif analysis revealed that SRSF10 binding to cassette exons was associated with exon inclusion, whereas the binding of SRSF10 within downstream constitutive exons was associated with exon exclusion. This positional effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
105
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 32 publications
6
105
0
Order By: Relevance
“…7). Together, these findings demonstrated that inclusion of exon5a by SRSF10 is consistent with activation mechanism for the protein in splicing regulation 19,21 , and strongly indicated that BCLAF1 is a direct splicing target regulated by SRSF10.…”
Section: Bclaf1-l Isoform Promotes Tumorigenesis Of Rko Cells In Micesupporting
confidence: 63%
See 4 more Smart Citations
“…7). Together, these findings demonstrated that inclusion of exon5a by SRSF10 is consistent with activation mechanism for the protein in splicing regulation 19,21 , and strongly indicated that BCLAF1 is a direct splicing target regulated by SRSF10.…”
Section: Bclaf1-l Isoform Promotes Tumorigenesis Of Rko Cells In Micesupporting
confidence: 63%
“…Strikingly, we found many purine-rich (GA rich) motifs especially within the downstream 200 bp region (5a3) of exon5a, and each constitutes a good match to the binding motif of splicing factor SRSF10 (previously known as SRp38; Supplementary Fig. 6a) 21,29 . Neither exon5 nor exon11 contained a match to the SRSF10 consensus sequence.…”
Section: Bclaf1-l Isoform Promotes Tumorigenesis Of Rko Cells In Micementioning
confidence: 91%
See 3 more Smart Citations